Ectopia lentis in Loeys‐Dietz syndrome type 4. Issue 8 (28th May 2020) - Braverman, Alan C.; Blinder, Kevin J.; Khanna, Sangeeta; Willing, Marcia
Abstract: Loeys‐Dietz syndrome is a heritable disorder of the connective tissue leading to multisystem involvement including craniofacial features, skeletal abnormalities, cutaneous findings and early‐onset and aggressive disease of the aorta and its branches. There are multiple types of Loeys‐Dietz syndrome related to pathogenic variants in TGFBR1, TGFBR2, SMAD3, TGFB2, and TGFB3 . Individuals with Loeys‐Dietz syndrome may be misdiagnosed as having Marfan syndrome due to shared phenotypic features and aortic root dilation. However, ectopia lentis has been an important discriminating feature, being unique to Marfan syndrome and not reported to be associated with Loeys‐Dietz syndrome. We report the case of a 46‐year‐old woman with Loeys‐Dietz syndrome type 4 due to a pathogenic variant in TGFB2 who was diagnosed with ectopia lentis at age 44. The patient underwent whole exome sequencing and no other pathogenic variants were found to explain the ectopia lentis. Our findings indicate that ectopia lentis may be an uncommon finding in Loeys‐Dietz syndrome type 4 and emphasize the importance of genetic testing in familial thoracic aortic aneurysm disease.